1995
DOI: 10.1177/036354659502300112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Icing Times in Decreasing Bone Metabolism and Blood Flow in the Knee

Abstract: In a previous study we used technetium-99m bone scans to show that cooling a knee for 20 minutes with a standard ice wrap will decrease soft tissue blood flow by a mean of 26%, and skeletal blood flow and metabolism by 19%. The present study examined the effects of shorter and longer icing periods to determine minimum cooling time for a measurable and consistent decrease, and time to produce maximal decrease within a safe period of icing (< 30 minutes). Thirty-eight subjects were studied. An ice wrap was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 7 publications
1
29
0
3
Order By: Relevance
“…C ryotherapy, which is the application of cold to an injured area, is a treatment protocol used to manage the magnitude of the inflammatory process, [1][2][3][4][5][6][7][8][9] blood flow, [10][11][12][13][14] initial swelling, [1][2][3][4][5][6]9,15 secondary injury, 1,[3][4][5][6][7][8][9]16,17 and pain. [1][2][3][5][6][7][8][9] Researchers have demonstrated that the application of external compression with cryotherapy greatly decreases both surface and intramuscular temperatures when compared with no compression.…”
mentioning
confidence: 99%
“…C ryotherapy, which is the application of cold to an injured area, is a treatment protocol used to manage the magnitude of the inflammatory process, [1][2][3][4][5][6][7][8][9] blood flow, [10][11][12][13][14] initial swelling, [1][2][3][4][5][6]9,15 secondary injury, 1,[3][4][5][6][7][8][9]16,17 and pain. [1][2][3][5][6][7][8][9] Researchers have demonstrated that the application of external compression with cryotherapy greatly decreases both surface and intramuscular temperatures when compared with no compression.…”
mentioning
confidence: 99%
“…Superficial cooling with ice application to the knee can reduce arterial blood flow by 38% in less than 5 minutes. 7,8 Olive et al 9 found similar reductions in brachial artery blood flow when comparing the effect of the application of Biofreeze and an ice pack over the forearm. Both modalities significantly reduced blood flow by $35% within the first 60 seconds of application.…”
Section: Mechanism Of Actionmentioning
confidence: 86%
“…Ice or cold packs (cryotherapy) at 0-1 C have been reported to alleviate pain and vasoconstrict vessels within the joint, limiting blood flow and inflammatory mediators (Ho et al 1994;Schroder and Passler 1994). The optimal length of the "ice effect" is 25 min, applied every hour as needed for pain and swelling (Ho et al 1994(Ho et al , 1995. The maximum length of application is recommended to be 30 min in order to avoid peroneal nerve palsy (Ho et al 1995).…”
Section: Controlling Inflammationmentioning
confidence: 99%
“…The optimal length of the "ice effect" is 25 min, applied every hour as needed for pain and swelling (Ho et al 1994(Ho et al , 1995. The maximum length of application is recommended to be 30 min in order to avoid peroneal nerve palsy (Ho et al 1995). Additional decrease in blood flow can be achieved with compression of the joint (Schroder and Passler 1994).…”
Section: Controlling Inflammationmentioning
confidence: 99%